2018
DOI: 10.4314/ahs.v18i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic proteins of normal pregnancy and pre-eclamptic patients in North West Nigeria

Abstract: BackgroundThe hypercoagulability of pregnancy is exaggerated in pre-eclamptic state because of endothelial activation with resultant production of some endothelial derived proteins that are said to be inhibitors of fibrinolysis. This study compares these proteins like tPA, PAI-1 and D-dimers in normal pregnant women and the pre-eclamptic women.MethodologyThis was a comparative cross-sectional study. Eighty-five pre-eclamptic women were recruited as subjects and eighty five age, trimester and parity matched nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…D-dimer is increased in normal pregnancy because of compensated state of low grade intravascular coagulation; Moreover, this increase shows that, inspite of the marked impairment in fibrinolytic potential; the fibrinolytic system remains functionally active. Previous research showed higher d-dimer concentrations in pregnant women with preeclampsia compared with normotensive pregnant women [18] [31] [32]. D-dimer is involved in the dynamic balance between plasminogen activators (t-PA and uPA) and plasminogen inhibitor (PAI-1) in women with preeclampsia [33] therefore, d-dimer concentration can reflect the dynamic changes in both the super-hypercoagulable status and the activated fibrinolytic state in preeclamptic patients [34] [35] [36].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer is increased in normal pregnancy because of compensated state of low grade intravascular coagulation; Moreover, this increase shows that, inspite of the marked impairment in fibrinolytic potential; the fibrinolytic system remains functionally active. Previous research showed higher d-dimer concentrations in pregnant women with preeclampsia compared with normotensive pregnant women [18] [31] [32]. D-dimer is involved in the dynamic balance between plasminogen activators (t-PA and uPA) and plasminogen inhibitor (PAI-1) in women with preeclampsia [33] therefore, d-dimer concentration can reflect the dynamic changes in both the super-hypercoagulable status and the activated fibrinolytic state in preeclamptic patients [34] [35] [36].…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 10 , 17 Preeclampsia has been associated with a hypercoagulable state. 24 Thrombotic microangiopathy comprises thrombotic thrombocytopenic purpura and atypical hemolytic uremic syndrome. Their common characteristics are occlusion of small arteries and capillaries and platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…84,100 Other procoagulant factors such as coagulation FVIII andvWF as well as markers of coagulation activation (such as D-dimer levels) have also been reported to be more significantly increased in pregnancies affected by preeclampsia relative to thoseobserved in the setting of normal, healthy pregnancy. 101 The enhanced procoagulant activity observed in preeclampsia is further augmented by a marked impairment in endogenous anticoagulant pathways, with antithrombin, protein C and free protein S activity all reported to be lower among women with preeclampsia in comparison to thoseobserved among the healthy pregnant population. 102,103 Derangements in the fibrinolytic pathway, with increased activation of fibrinolysis but also with increased fibrin formation and increased plasminogen activator inhibitor-1 (PAI-1, an endogenous inhibitor of fibrinolysis) levels, have also been described in preeclampsia and appear to favour an even more marked impairment in fibrinolytic activity than that observed in healthy pregnancy.…”
Section: Blood Coagulation and Fibrinolytic-pathway Derangements In Pmentioning
confidence: 99%
“…102,103 Derangements in the fibrinolytic pathway, with increased activation of fibrinolysis but also with increased fibrin formation and increased plasminogen activator inhibitor-1 (PAI-1, an endogenous inhibitor of fibrinolysis) levels, have also been described in preeclampsia and appear to favour an even more marked impairment in fibrinolytic activity than that observed in healthy pregnancy. 101,104 Platelet Activity in Preeclampsia Platelets play a key role in physiological haemostasis by forming the initial 'platelet plug' at the site of vascular defects and by supporting thrombin generation by releasing various procoagulant substances following activation (such as vWF, factor V, fibrinogen, platelet factor-4, etc.). Platelets also support thrombin generation and fibrin formation through the expression of anionic phospholipids on their cell surface which act as co-factors for the procoagulant activity of the intrinsic andextrinsic tenase and prothrombinase complexes.…”
Section: Blood Coagulation and Fibrinolytic-pathway Derangements In Pmentioning
confidence: 99%